Atorvastatin Increases the Expression of Long Non-Coding RNAs ARSR and CHROME in Hypercholesterolemic Patients: A Pilot Study - Isis Paez; Yalena Prado; Carmen G. Ubilla; Tomás Zambrano; Luis A. Salazar (MDPI AG, 2020)
Atorvastatin is extensively used to treat hypercholesterolemia. However, the wide interindividual variability observed in response to this drug still needs further elucidation. Nowadays, the biology of long non-coding RNAs (lncRNAs) is better understood, and some of these molecules have been related to cholesterol metabolism. Therefore, they could provide additional information on variability in response to statins. The objective of this research was to evaluate the effect of atorvastatin on three lncRNAs (lncRNA ARSR: Activated in renal cell carcinoma (RCC) with sunitinib resistance, ENST00000424980; lncRNA LASER: lipid associated single nucleotide polymorphism locus, ENSG00000237937; and lncRNA CHROME: cholesterol homeostasis regulator of miRNA expression, ENSG00000223960) associated with genes involved in cholesterol metabolism as predictors of lipid-lowering therapy performance. Twenty hypercholesterolemic patients were treated for four weeks with atorvastatin (20 mg/day). The lipid profile was determined before and after drug administration using conventional assays. The expression of lncRNAs was assessed in peripheral blood samples by RT-qPCR. As expected, atorvastatin improved the lipid profile, decreasing total cholesterol, LDL-C, and the TC/HDL-C ratio (p < 0.0001) while increasing the expression of lncRNAs ARSR and CHROME (p < 0.0001) upon completion of treatment. LASER did not show significant differences among the groups (p = 0.50). Our results indicate that atorvastatin modulates the expression of cholesterol-related lncRNAs differentially, suggesting that these molecules play a role in the variability of response to this drug; however, additional studies are needed to disclose the implication of this differential regulation on statin response.